Sleep in Children With Pallister Killian Syndrome: A Prospective Clinical and Videopolysomnographic Study - Fetta, Anna; Di Pisa, Veronica; Ruscelli, Martina; Soliani, Luca; Sperti, Giacomo; Ubertiello, Sara; Ricci, Emilia; Mainieri, Greta; Rocca, Alessandro; Mancardi, Maria Margherita; Giordano, Lucio; Pruna, Dario; et al. (Frontiers in Neurology, 2021)
Objectives: Pallister-Killian syndrome (PKS) is a rare genetic disorder with multi-organ involvement caused by mosaic tetrasomy of chromosome 12p. Although many caregivers report the presence of impaired sleep in their children, there are no clear data in the literature on this issue and no systematic study has ever been performed. With this study, we aimed to characterize the features of sleep in Pallister-Killian syndrome and identify the possible influence of clinical and demographic features. Moreover, our aim was to verify the effectiveness of conventional screening questionnaires in this particular group of patients. Methods: We prospectively enrolled 14 patients aged 1–17 years in collaboration with PKS Kids Italia ONLUS. The Sleep Disturbance Scale for Children (SDSC) questionnaire was administered to caregivers. Then, video polysomnography (VPSG) of at least 24 h was performed and results were compared with a same-aged control group. Results: A total of 92% of patients had abnormal SDSC scores, extremely high in the “disorder of initiating and maintaining sleep” (DIMS) and “sleep breathing disorders” (SBD) subscales. VPSG showed a significantly impaired macrostructure in PKS patients, with a higher Arousal Index (p < 0.00001) and percentage of time spent in N3 (p < 0.00001), and reduced Sleep Efficiency (p = 0.0006). After dividing both PKS and controls into two groups based on median age, some peculiarities emerged: the younger group had higher Awakenings Index (p = 0.0207) and percentage of time spent in N1 (p = 0.015) while the older group showed higher time in bed (TIB) (p = 0.0485), compared with controls. Due to poor compliance, the Apnea-Hypopnea Index (AHI) was evaluated only for 10 PKS children, being significantly increased (p = 0.0427) compared with controls. SBD subscale scores in SDSC were significantly related to AHI values in VPSG (p = 0.0099). Conclusions: This study constitutes the first attempt to describe the sleep pattern in PKS. Despite small numbers due to the rarity of the syndrome, our VPSG results confirm the high prevalence of sleep disorders (SDs) in these patients. It is therefore essential to investigate and treat them. The SDSC scale is a good screening tool for early detection also in these patients, with particular sensitivity in detecting breathing disorders.